Enhancing microalgal lipid accumulation for biofuel production - Zhu, Zhi; Sun, Jing; Fa, Yun; Liu, Xufeng; Lindblad, Peter (Frontiers in Microbiology, 2022)
Microalgae have high lipid accumulation capacity, high growth rate and high photosynthetic efficiency which are considered as one of the most promising alternative sustainable feedstocks for producing lipid-based biofuels. However, commercialization feasibility of microalgal biofuel production is still conditioned to the high production cost. Enhancement of lipid accumulation in microalgae play a significant role in boosting the economics of biofuel production based on microalgal lipid. The major challenge of enhancing microalgal lipid accumulation lies in overcoming the trade-off between microalgal cell growth and lipid accumulation. Substantial approaches including genetic modifications of microalgal strains by metabolic engineering and process regulations of microalgae cultivation by integrating multiple optimization strategies widely applied in industrial microbiology have been investigated. In the present review, we critically discuss recent trends in the application of multiple molecular strategies to construct high performance microalgal strains by metabolic engineering and synergistic strategies of process optimization and stress operation to enhance microalgal lipid accumulation for biofuel production. Additionally, this review aims to emphasize the opportunities and challenges regarding scaled application of the strategic integration and its viability to make microalgal biofuel production a commercial reality in the near future.